Minding their own business : Zambia. - Martin, Antony (Harmondsworth : Penguin Books, 1975)
Bibliotheek François Vercammen
Titel op de kaft: Minding their own business : Zambia's struggle against Western control
Engels
Monografie
Keywords: onafhankelijkheid; economie; Zambia